IMPLEMENTATION OF THE LEAN SIX SIGMA METHOD TO REDUCE WASTE DEFECT IN THE PRODUCTION PROCESS AT CV JF COLLECTION MAYONG JEPARA (Science and Technology (SciTech), 2022)
CV JF Collection is a manufacturing company engaged in the manufacture of bags. There is still a lot of waste found in the production process, where the sewing process is the process that has the most waste, especially defect waste and provides considerable losses for the company compared to the material selection process, the cutting process. ), and the finishing process. The method of repairing waste defect carried out by the company is currently still not effective. This results in losses for the company. From these problems, this research was carried out by providing suggestions for improvements that aim to minimize waste defects that occur in the sewing process. This research is a type of quantitative research that examines the use of the Lean Six Sigma method. Where Value stream mapping is used to describe the physical flow and information that occurs in the production process. Based on the identification of waste that has been carried out, several types of defects were obtained. Furthermore, the calculation of process capability for each type of defect is carried out. The results of the process capability show the sigma level value for each defect. Then an analysis of the root causes of the waste defect is carried out for each type of defect using a fishbone diagram. After the root cause of the waste defect has been found, recommendations for improvement are given using Failure Mode and Effect Analysis (FMEA). Then the sigma level calculation is carried out again to determine whether or not the sigma level has increased after the proposed improvement is given.